Neuroimaging Study Investigating the Supraspinal Control of Lower Urinary Tract Function in Man With Orthotopic Ileal Neobladder - Wu, Wanhua; Su, Yun; Huang, Hao; Chen, Meiwei; Fan, Fan; Zhu, Dingjun; Li, Kaiwen; Guo, Zhenghui; Liang, Zhiying; Huang, Hai (Frontiers in Surgery, 2021)
Introduction: Recent studies employing functional imaging methodology demonstrated the reference brain regions of urinary tract function, including midbrain periaqueductal gray, thalamus, cingulate and prefrontal cortex. Orthotopic ileal neobladder is a desirable method of urinary diversion after radical cystectomy, but its supraspinal control are still unknown. Our aim was to evaluate brain activity while urgency and voluntary urinary control in male subjects with ileal orthotopic neobladder by performing functional magnetic resonance imaging(fMRI) during a block design experiment. Materials & methods: patients were recruited in Sun Yat-sen Memorial Hospital of Sun Yat-sen University from October 2017 to May 2019. Two tasks had been taken during fMRI scan. 1) Repeatedly infused and withdrew sterile saline solution into and out of the neobladder to simulated urgency ,2) Repeatedly contracted pelvic floor muscle with full neobladder to induce an inhibition of the micturition, since the subjects were asked not to urinate. The obtained data were visualized and statistically analyzed. Results: Sixteen subjects were recruited in the study and complete data were obtained from 10 subjects, mean age 60.1 years, average postoperative time 20.2 month, daytime continence rate 100%. ParaHippocampal, Frontal Lobe, Vermis and anterior cingulate cortex were activated at large bladder volumes, and Thalamus and Caudate Nucleus were deactivated while voluntary urinary control. Conclusion: A Complex supraspinal program is involved during ileal orthotopic neobladders control which are significantly different from normal bladders, in which the original intestine visceral volume sensation is preserved.